Is There a Difference in Graft Motion for Bone-Tendon-Bone and Hamstring Autograft ACL Reconstruction at 6 Weeks and 1 Year?. (October 2016) - Irvine, James N.; Arner, Justin W.; Thorhauer, Eric; Abebe, Ermias S.; D'Auria, Jennifer; Schreiber, Verena M.; Harner, Christopher D.; Tashman, Scott
Background: Bone–patellar tendon–bone (BTB) grafts are generally believed to heal more quickly than soft tissue grafts after anterior cruciate ligament (ACL) reconstruction, but little is known about the time course of healing or motion of the grafts within the bone tunnels. Hypothesis: Graft-tunnel motion will be greater in hamstring (HS) grafts compared with BTB grafts and will be less at 1 year than at 6 weeks. Study Design: Controlled laboratory study. Methods: Twelve patients underwent anatomic single-bundle ACL reconstruction using HS or BTB autografts (6 per group) with six 0.8-mm tantalum beads embedded in each graft. Dynamic stereo x-ray images were collected at 6 weeks and 1 year during treadmill walking and stair descent and at 1 year during treadmill running. Tibiofemoral kinematics and bead positions were evaluated. Graft-tunnel motion was based on bead range of motion during the loading response phase (first 10%) of the gait cycle. Results: During treadmill walking, there was no difference in femoral tunnel or tibial tunnel motion between BTB or HS grafts at 6 weeks (BTB vs HS: 2.00 ± 1.05 vs 1.25 ± 0.67 mm [femoral tunnel]; 1.20 ± 0.63 vs 1.27 ± 0.71 mm [tibial tunnel]), or 1 year (BTB vs HS: 1.62 ± 0.76 vs 1.08 ± 0.26 mm [femoral tunnel]; 1.58 ± 0.75 vs 1.68 ± 0.53 mm [tibial tunnel]). During stair descent, there was no difference in femoral or tibial tunnel motion between BTB and HS grafts at 6 weeks or 1 year. With running, there was no difference between graft types at 1 year. For all results, P values were > .05. Knee kinematics were consistent with the literature. Conclusion: During walking and stair descent, ACL reconstruction using suspensory fixation yielded no difference between graft types in femoral or tibial tunnel motion at 6 weeks or 1 year. All subjects were asymptomatic with knee kinematics similar to that of the literature. The significance of persistent, small (1 to 3 mm) movements at 1 year for healing or graft performance is unknown. Clinical Relevance: These study results may have significant implications for graft choice, rehabilitation strategies, and timing for return to sports.